Формування української археології в Галичині у ХІХ столітті: Ісидор Шараневич (1829–1901) - Булик, Н. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Process of formation of Ukrainian archaeologyin Halychyna in XIX century is analyzed at the article. Preconditions of rise and transition to professional researches are explored. Two stages of process of development of archaeological science are distinguished. First of them includes 1818–1870 – period of Romantism in Halych archaeology. During the second period Isidor Sharanevych played main part in establish of Ukrainian archaeology. Field researches carried out by this scientist are presented. Main attention is paid to his excavations in Chekhy and Vysots’ko, his work on the Chair of Austrian history of L’viv University, participation in organization of archaeological departments in museums of Stavropigia and the University. Cultural and monument-preservation activity of Isidor Sharanevych is emphasized. Place of scholar’s works dedicated to archaeological issues among his scientific heritage is cleared up.